Pembelajaran Bahasa Indonesia pada Kurikulum Merdeka Berbasis Ekologi Bahasa di SMK Pariwisata Lombok Timur - Muh. Jaelani Al Pansori; Moh. Irfan; Herman Wijaya; Brillianing Pratiwi (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
A language ecology study at Lombok Tourism Vocational Schools is essential to meet students’ learning needs and to prepare qualified human resources for the tourism sector in East Lombok. This research aims to explore the specific needs of Indonesian language learning relevant to the Merdeka Curriculum within an Indonesian language ecology framework, enhance instructional effectiveness, and propose strategies for integrating these learning needs with the context of the local tourism industry. This study employed an exploratory research design with a language ecology approach. Data were collected through observations, interviews, document analyses, focus group discussions (FGDs), and questionnaires. The data collection encompassed an analysis of learning processes and outcomes, structured interviews regarding ecological environments and the use of learning materials, as well as observations of language ecology in tourism vocational schools located in coastal, urban, and mountainous areas. Data were analyzed descriptively by quantifying learning needs based on ecological environments, correlating the quantitative findings with interview and FGD data, and drawing qualitative conclusions on the distinctions of Indonesian language learning needs across tourism schools. The findings indicate that Indonesian language learning aligned with the Merdeka Curriculum and informed by language ecology should emphasize communication skills in both formal and informal contexts, tourism-related vocabulary, and the integration of Lombok’s local cultural values. These needs highlight the role of language as a key instrument in preparing students for the tourism workforce. The ecological approach was found to enhance instructional relevance and support students’ understanding of language use in real-world professional settings. Recommended strategies include project-based learning through tourism simulations and the development of instructional materials integrating language with local traditions, folklore, and cultural terminology to strengthen students’ contextual language competence.